2020
DOI: 10.1016/j.annonc.2020.08.2287
|View full text |Cite
|
Sign up to set email alerts
|

LBA54 Randomized phase III trial of nivolumab in combination with carboplatin, paclitaxel, and bevacizumab as first-line treatment for patients with advanced or recurrent non-squamous NSCLC

Abstract: Background: Nivolumab has been approved as second or later line therapy for NSCLC. It is becoming evident that cytotoxic chemotherapy and angiogenesis inhibitors may enhance therapeutic benefits of immune checkpoint inhibitors such as nivolumab. ONO-4538-52/TASUKI-52 is the first randomized, double-blinded phase III trial of nivolumab plus platinum chemotherapy with bevacizumab for first-line treatment of non-squamous NSCLC.Methods: Between May 2017 and June 2019, treatment-naïve stage IIIB/IV or recurrent nsq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Anlotinib provide a potential for patients who unable to benefit from chemotherapy, immunotherapy and EGFR-mutation target agent (6). In the IMpower150 and TASUKI-52 trials, ICIs combined with angiogenic inhibitors and chemotherapy showed a significant PFS benefit in NSCLC patients compared to the combination of angiogenic inhibitors and chemotherapy (18,19). At the World Conference on Lung Cancer (WCLC) in 2019, a phase 1 trial with sintilimab (ICI) plus anlotinib as first-line treatment in advanced NSCLC patients without oncogenic driver mutations showed encouraging results (20).…”
Section: Discussionmentioning
confidence: 99%
“…Anlotinib provide a potential for patients who unable to benefit from chemotherapy, immunotherapy and EGFR-mutation target agent (6). In the IMpower150 and TASUKI-52 trials, ICIs combined with angiogenic inhibitors and chemotherapy showed a significant PFS benefit in NSCLC patients compared to the combination of angiogenic inhibitors and chemotherapy (18,19). At the World Conference on Lung Cancer (WCLC) in 2019, a phase 1 trial with sintilimab (ICI) plus anlotinib as first-line treatment in advanced NSCLC patients without oncogenic driver mutations showed encouraging results (20).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias of included RCTs is summarized in Supplementary File: Figure S1. Two trials were judged as unclear risk of bias [22,26]. The remaining trials were rated with a low risk of bias.…”
Section: Assessment Of Included Studies and Publication Biasmentioning
confidence: 99%
“…Finally, 17 eligible articles (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) reporting 15 RCTs (14 phase 3 and 1 phase 2 trials) with 10,358 patients (1,199 with and 9,159 without asymptomatic/treated BMs) were included in the meta-analysis. Most of the RCTs (3,(5)(6)(7)(8)(9)(11)(12)(13)(14)(15)(16)(17)(18) stated clearly that patients with meningeal metastasis were excluded, whereas the other three trials (4,10,19) did not provide information for whether patients with meningeal metastasis were excluded. The clinical and demographic characteristics of included studies are shown in Table 1 and Supplementary File: Table S3.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…The risk of bias in included RCTs is summarized in Supplementary File, Figure S1. Only one trial (19) was judged as having an unclear risk of bias, as it had more than three domains for indicating them an unclear risk. The remaining trials were rated with a low risk of bias.…”
Section: Assessment Of Included Studies and Publication Biasmentioning
confidence: 99%
See 1 more Smart Citation